1181. Use of the Combination Antibiogram in the Era of MDR Gram-Negative Pathogens. (26th November 2018) - Klinker, Kenneth; Cherabuddi, Kartikeya; Redell, Mark; Balogh, Matthew; Massey, Jill; Dudley, Michael
Abstract: Background: Combinations of two or more antimicrobial agents are frequently used in empiric therapy regimens to ensure at least one agent demonstrates activity against suspected pathogens. A combination antibiogram can assess the increase in empiric coverage of a particular combination vs. either of the agents alone (i.e., percent gain). These data could assist in developing empiric regimens that may be particularly useful in settings with problematic multidrug-resistant Gram-negative pathogens. Methods: An Excel-based model to construct combination antibiograms was developed to assist clinicians in evaluating institutional susceptibility data. The University of Florida Health Shands Hospital microbiology laboratory supplied susceptibility data for ceftriaxone (CFX), cefepime (CEF), ciprofloxacin (CIP), and amikacin (AMI) to assess % gain achieved with combinations for E. coli all blood isolates ( n = 206) and blood isolates with an ESBL phenotype ( n = 35). The same laboratory provided susceptibility data for CEF, piperacillin–tazobactam (PTZ), AMI and CIP for P. aeruginosa (all, n = 250; carbapenem-resistant (CARB-R), n = 30). Results: Percent gains achieved by adding AMI or CIP to CFX and CEF to capture at least one agent exhibiting in vitro susceptibility against all blood E. coli were calculated: CFX-AMI, 16%; CFTX-CIP, 3%; CEF-AMI, 10%; CEF-CIP, 1%. The percentage gain specific to E. coli blood isolates with an ESBL phenotype ranged from 9% to 86%. The combination with the greatest percent loss against blood E. coli isolates, comparing all blood isolates to those with an ESBL phenotype, was CFX-CIP (∆-66%). Percentage gain achieved against all isolates of Pa by adding AMI or CIP to PTZ and CEF were CEF-AMI, 8%; CEF-CIP, 5%; PTZ-AMI, 15%; PTZ-CIP, 9%; percent gain of the same combinations against P. aeruginosa CARB-R isolates were 23%, 10%, 47%, and 30%, respectively. Adding AMI to either β-lactam: PTZ % S increased from 47% to 77% (+CIP) and to 94% (+AMI); CEF % S increased from 60% S to 70% (+CIP) and to 83% (+AMI). Conclusion: Combination antibiogram models can assist clinicians in identifying regimens which may provide improved targeting of MDR phenotypes through calculation of percent gain. Disclosures: K. Klinker, Melinta Therapeutics: Consultant, Speaker honorarium. Nabriva Therapeutics: Scientific Advisor, Consulting fee. M. Redell, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary. M. Balogh, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary. J. Massey, Melinta Therapeutics, Inc.: Employee and Shareholder, Salary. M. Dudley, The Medicines Company: Employee, Salary.